POLA KONSUMSI AIR, SUSU DAN PRODUK SUSU, DAN MINUMAN MANIS SEBAGAI FAKTOR RISIKO OBESITAS PADA ANAK SEKOLAH DASAR DI KOTA YOGYAKARTA DAN KABUPATEN BANTUL - , Yayah Lakoro ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Sweet drinks are suspected as the cause of the incidence of obesity in children. Unhealthy milk and milk product containing fat and high glucose can become one of risk factors of the incidence of obesity whereas water is healthy drink without calori that can help manage weight. Objective: To identify consumption pattern of drinks in obese children Probability Proportional to Size (PPS) Method: The study was a case control study, involving obese elementary school children as cases and elementary school children with normal weight as control. Locations of the study were Yogyakarta Municipality and District of Bantul. Sampling method used . There were 488 samples comprising 244 cases and 244 controls. Matching was made to the school of origin on condition that case and control students were at the same grade. Statistical test used McNemar and logistic regression to identify variables of risk factors. Result: There was difference in characteristics of gender between the two groups (P=0.03). Average amount of water and sweet drink consumption in obese children significantly differed from non obese children, subsequently 243.8 mL/day (Â±2Â½ cup/day) and 397.3 mL/day (Â± 2 cup/day), whereas avarage amount of consumption of unhealthy milk and milk product in obese and non obese children showed no significant difference. The result of McNemar test showed that consumption of water and sweet drink was associated with the incidence of obesity in children at Yogyakarta Municipality and District of Bantul with score of OR 2.1(95% CI:1.4 â 3.05) and OR 3.1 (95% CI:2.1 â 4.5), whereas consumption of unhealthy milk and milk product showed no significant difference. The result of regression test showed that sweet drink was dominant risk factor of the incidence of obesity in children (RÂ²= 0.071). Conclusion: Consumption of water and sweet drink was associated with the incidence of obesity in children. Consumption of sweet drink could affect consumption of water, whereby higher comsumption of sweet drink meant lower consumption of water. Nutrition education embedded in the curriculum could be used as an alternative of obesity prevention in children by changing or building healthy lifestyle.